The Diagnostic Thinking of Psychologist and it’s Forming in the System of Professional Preparation - Busheva, T. V. (Psychological Prospects Journal, 2012)
The problem of essence, specifics, descriptions of the diagnostic thinking of psychologist is examined in the article. Psychological and pedagogical terms and ways of forming of the diagnostic thinking of students-psychologists are determined in the system of professional preparation.
Keywords: diagnostic thinking of psychologist description of the diagnostic thinking forming